Contact with Primary Care: The Experience of People with Intellectual Disabilities. Issue 3 (13th September 2013) - Perry, Jonathan; Felce, David; Kerr, Mike; Bartley, Stuart; Tomlinson, Judith; Felce, Janet
<x xml:space="preserve">Abstract</x> Background People with intellectual disabilities experi‐ence disparities in their health and health care. Annual health checks are intended to counter such disparity by improving access to primary health care. However, little is known about their experience of having a health check or other types of contact with primary care services. Materials and Methods The findings of two studies which used focus groups were combined. 102 people with intellectual disabilities participated in the focus groups. Results Participants' experiences of primary care services generally, and health checks in particular, were positive. However, unanimity was rare on any of the topics discussed and a number of areas of dissatisfaction emerged. Conclusions Further studies with larger and more representative samples are necessary as feedback from people with intellectual disabilities about their experience of contact with primary care staff might help to enhance GP knowledge about their health requirements.